Clinical Outcomes of Clofazimine Use for Rapidly Growing Mycobacterial Infections. (20th October 2019) - Carey, George B; Tebas, Pablo; Vinnard, Christopher; Kim, Deborah; Hadjiliadis, Denis; Hansen-Flaschen, John; Dorgan, Daniel; Glaser, Laurel; Barton, Grant; Hamilton, Keith W
Abstract: Background: Rapidly growing mycobacteria (RGM) have high rates of intrinsic antibiotic resistance and require prolonged antibiotic therapies associated with considerable toxicity. Less toxic and more effective therapies are needed. One promising agent is clofazimine (CFZ), an antibiotic with favorable in vitro data but limited clinical data in RGM. Methods: We performed a retrospective cohort study of all patients treated for RGM infection with a CFZ-containing regimen in the University of Pennsylvania Health System between January 1, 2010, and December 31, 2016. The primary outcome was clinical cure, defined as no evidence of clinical or microbiologic infection recurrence 1 year after the completion of treatment. Secondary outcomes included clinical, radiologic, and microbiologic response; all-cause mortality; infection-specific mortality; and treatment-related adverse events. Descriptive and unadjusted analyses were performed to elucidate associations between pertinent demographic and comorbidity data, clinical presentation, treatment history, and treatment outcomes. Results: We treated 55 patients with CFZ for RGM infection during the study period, in combination with a median of 5 other antibiotic agents during each treatment course. Clinical cure with initial treatment regimen was achieved in 43% of patients with pulmonary infection and 71% of patients with nonpulmonary infection. CFZ was well tolerated in our cohort and was discontinued prematurely in 20% of patients, but only in the context of discontinuing all antibiotic agents. Conclusions: As part of multidrug therapy, CFZ is well tolerated and may be effective in patients with RGM infection, especially nonpulmonary and non– Mycobacterium abscessus complex infections. Abstract : Rapidly growing mycobacteria (RGM) have high rates of antibiotic resistance, often requiring intravenous antibiotics that have substantial toxicity. This study demonstrates that clofazimine, an oral riminophenazine antibiotic, may be safe and effective in patients with RGM infection.